Impacto físico e financeiro da desocupação de área de preservação permanente (app) explorada por uma salina de grande porte do Rio Grande do Norte - Farias, Rodolfo Rodrigo Souza (Universidade Federal Rural do Semi-Árido, 2019)
Brazilian production is mostly concentrated in the Costa Branca region, becoming important for Brazil. Why studies and surveys, understanding how a company's market for basic and superior products this year is considered a superior product. After the “Operation Ouro Branco” held in 2013, some companies in the sector were fined for illegal occupation of APP, starting a discussion on what to do to be a regularization. Due to the scarcity of documents that list as steps and costs of the execution of the dialogue unfolding, environmental recovery and the new productive generation, the objective was to plan a cost composition model for this work, as well as the value of the economic impact, including the annual loss of annual production. Therefore, the case study of Salina Araguassú, located in Porto do Mangue/RN, made it possible to collect data in order to obtain a occupied APP area, as well as the volume of earth movement required for its vacancy. Thus, the calculation of the value of the work at R$ 6,445,948.60, having as IE R $ 8,644,078.60, and the amount of perpetual loss in the house of R$ 45,587,442.77. Thus, the inoccupation of PPA is not the one that is around the world, because of the high content of waves of regions, sometimes hindering the development of vascular vegetation. Therefore, other alternatives need to be observed.
Artigo
Keywords: Manguezal; Compensação Ambiental; Ecossistema; Preservação Ambiental; Mangrove; Environmental compensation; Environmental; Preservation ecosystem; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA